2006
DOI: 10.3844/ajptsp.2006.65.71
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Phyllanthus Species: Induction of TNF-α-mediated Apoptosis in HepG2 Hepatocellular Carcinoma Cells

Abstract: Phyllanthus species, especially P. amarus is a medicinal plant with hepatoprotective activity, believed to occur in part by inhibiting hepatitis B virus function. The pathogenesis mechanism of viral hepatitis is closely related to hepatocyte necrosis apoptosis. The aim of our study was to investigate the in vitro effects of extracts from three Phyllanthus species, P. urinaria, P. amarus and P. debilis in regulating cell proliferation and gene expression activities of HepG2 hepatocellular carcinoma cells. All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
(29 reference statements)
2
7
0
1
Order By: Relevance
“…These findings demonstrated that Phyllanthus extracts induce TNF-␣ production from the hepatocellular carcinoma cells while inhibiting production of potent anti-apoptotic genes IL-8 and COX-2. Untreated cells (control) received only 0.01% DSMO (Sureban et al, 2006). Two human leukaemia cell lines were employed: K-562 and its vincristine-resistant counterpart Lucena-1, and Pgpoverexpressing subline to evaluate the possible cytotoxic effect and multidrug resistance (MDR) reversing properties of the extract and compounds isolated from P. amarus.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…These findings demonstrated that Phyllanthus extracts induce TNF-␣ production from the hepatocellular carcinoma cells while inhibiting production of potent anti-apoptotic genes IL-8 and COX-2. Untreated cells (control) received only 0.01% DSMO (Sureban et al, 2006). Two human leukaemia cell lines were employed: K-562 and its vincristine-resistant counterpart Lucena-1, and Pgpoverexpressing subline to evaluate the possible cytotoxic effect and multidrug resistance (MDR) reversing properties of the extract and compounds isolated from P. amarus.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…All of them traditionally have been used for the treatment of many ailments such as gonorrhea, jaundice, diabetes and liver diseases [13]. The anticancer activity of Phyllanthus species has also been documented [14,15,16,17,18,19]. For example, P. amarus inhibits the growth of human adenocarcinoma cell line Caco-2 [14], hepatoma induced by N -nitrosodiethylamine in rats [15] and sarcoma induced by 20-methylcholanthrene in mice [16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, P. amarus inhibits the growth of human adenocarcinoma cell line Caco-2 [14], hepatoma induced by N -nitrosodiethylamine in rats [15] and sarcoma induced by 20-methylcholanthrene in mice [16]. Similarly, P. urinaria has also been shown to possess cytotoxic activity against several cancer cell lines including human promyelocytic leukemia [17], Lewis lung carcinoma cells [18] and HepG2 cells [19]. However, the pharmacological studies on P. virgatus mostly involved its antimicrobial [20,21] and antihyperglycemic effects [22].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer tissue/tumor inhibition and elimination effects of V. amygdalina have been obtained in various studies (Guruswamy and Benbrook, 2006;Sureban et al, 2006;Constance Ikoku, 2009), although no case of use of V. amygdalina to treat human cancer has been reported. A Nigerian born professor of biology, a specialist in Vernonia amygdalina; at Jackson State University, Mississippi; found that some compounds from V. amygdalina extracts, were able to inhibit the growth of breast cancer and were also effective in other tumor cells (Oyugi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%